A106 SEROPREVALENCE OF EPSTEIN-BARR VIRUS AND ASSOCIATION WITH DISEASE CHARACTERISTICS IN PEDIATRIC PATIENTS WITH NEW ONSET IBD - Kornitzer, G A (J Can Assoc Gastroenterol, 2019)
BACKGROUND: While the mechanism of Inflammatory Bowel Disease is not yet fully understood, we know that these diseases are auto-inflammatory conditions. As such, we treat them with immune-modulating agents. It has been shown in populations of IBD patients that there is an increased risk of complications such as lymphoproliferative disease, whether due to inherent immune dysfunction, long term effects of treatments or other factors, such as Epstein-Barr viral infection. AIMS: The aim of our study is to determine EBV seroprevalence in our patient population at diagnosis, to assess impact on disease presentation, and to identify patients at risk for potential complications related to therapies used. METHODS: Retrospective chart review was done for all patients followed by the Gastroenterology department at CHU Sainte-Justine over a two year period with new onset IBD between January 2016 and December 2017. A total of 216 patients were identified. 10 patients were excluded: 4 with no confirmed IBD, 1 diagnosis before 2016, 5 incomplete charts at diagnosis. RESULTS: Of 206 patients included, 120 patients had EBV serologies available around diagnosis, with 53 patients (44.2%) IgG seropositive (VCA and/or EBNA). 2 patients were IgM seropositive, suggesting active infection. When stratified by age, prevalence of seropositivity was, for 0 to <10 years 36% (total = 25), 10 to <17 years 46% (total = 87), and 17 + years 50% (total = 8). When comparing disease characteristics between groups, there was similar incidence of IBD classification: in seronegative patients 61.2 % Crohn’s disease (CD), 38.8% Ulcerative Colitis (UC) and IBD unclassified (IBDU), and in seropotivie 69.8 % CD and 30.2% UC and IBDU. Similar distributions were found of disease phenotype according to the Paris classification, 73.1% B1 (nonstricturing nonpenetrating) in seronegative patients compared to 73.6% B1 in the seropositive group. In addition, distribution of biochemical markers of disease severity at diagnosis (hemoglobin, CRP, SR and ALT) and disease activity scores were similar in both groups. CONCLUSIONS: The seroprevalence of EBV at diagnosis of IBD resembles that of the general population, where risk of previous exposure increases with age. While we were unable to show a significant difference in disease presentation at diagnosis within our population, these patients remain potentially at risk for reactivation and lymphoproliferative complications of EBV with relation to immune-modulating therapies. Our future studies will be looking at EBV reactivation, changes in viral load and impact on disease progression in our patients undergoing treatment for IBD. Larger cohorts are needed to identify potential relationship between EBV and immune dysfunction-related IBD. FUNDING AGENCIES: None